47. EFFECTIVENESS OF THE MEDICINAL RECIPE HOANG KY QUE CHI NGŨ VỰT THANG ON PATIENTS WITH NERVE ROOT COMPRESSION SYNDROME TREATED AT THE HOSPITAL OF TRADITIONAL MEDICINE IN CAN THO CITY (Vietnam Journal of Community Medicine, 2025)
Research objective: Compare the effectiveness of the treatment regimen containing Astragalus membranaceus, Cinnamon, and Five Elements Decoction in improving nerve root syndrome and the basic regimen in patients with nerve root compression syndrome treated as inpatients at Can Tho City Traditional Medicine Hospital.Research subjects and methods: Clinical intervention study with a control group, comparing the effectiveness before and after treatment in 2 groups of patients with nerve root compression syndrome. Results: Through the survey, the age group of 40-59 has the highest proportion, the medicine Astragalus membranaceus and five elements is effective in treating nerve root compression assessed by VAS from 7.43 ± 0.82 to 2.43 ± 0.85, Oswestry score from 35.48 ± 3.94 decreased to 11.27 ± 2.41, Lasègue test, Valleix test, bell sign improved after 14 days of treatment (p
Keywords: Astragalus, Cinnamon, Five-ingredient Decoction; Herniated disc; Spinal degeneration; nerve root compression syndrome